1986
DOI: 10.1111/j.1754-4505.1986.tb01589.x
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric dentistry and the child with asthma

Abstract: A child with asthma who needs dental treatment can be a source of concern to the pediatric dentist. Recent studies have provided a better understanding of the pathophysiology of asthma as well as the role of emotions in the expression of asthma. The goal in managing the patient with asthma is to prevent an acute asthmatic episode during the dental procedure. Suggestions are made to meet this goal. Asthma does not require alteration of routine dental practices and, most importantly, the well-managed child with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…On the other hand, Mungo et al 16) found that cotton rolls could trigger a hyperreactive airway response in a sensitive subject. Rubber dam should be used judiciously to avoid possible respiratory compromise or aggravation 17) .…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, Mungo et al 16) found that cotton rolls could trigger a hyperreactive airway response in a sensitive subject. Rubber dam should be used judiciously to avoid possible respiratory compromise or aggravation 17) .…”
Section: Discussionmentioning
confidence: 98%
“…(15,16) Rapid hemostasis in a wound occur when thrombin is applied, as it converts fibrinogen to fibrin. When used along with antifibrinolytic agents, topical fibrin glue can reduce the amount of factor replacement (17) It is not so we have to always stop ASA therapy , as local hemostatic measures are sufficient to control bleeding but if it has to be withdrawn , it should be done at least 10 days before surgery. INR(2.0-3.0)is very important to be measured before any surgical procedure specially in patients taking warfarin, if INR is less than 3.0, most oral surgical procedures can be performed without altering the warfarin dose.…”
Section: Oral Surgerymentioning
confidence: 99%